2017
DOI: 10.3390/nano7020046
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of a Three-Dimensional Porous Multi-Walled Carbon Nanotube Scaffold for Bone Regeneration

Abstract: Carbon nanotubes (CNTs) have attracted a great deal of attention for the biological and medical science fields because of their characteristic physical and biological properties. In this study, we investigated the capacity of the 3D porous CNT scaffold (CNT porous block; CNTp) for bone regenerative medicine. Surface observations using a scanning electron microscope (SEM), crystal depositions on the surface of CNTps immersed in simulated body fluid (SBF), and evaluations of protein adsorption and controlled rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
(53 reference statements)
1
26
0
1
Order By: Relevance
“…Thanks to this, they are increasingly applied in medicine and diagnostics, including tissue engineering [1,2]. These two-dimensional carbon structures are used, among others, to functionalize materials designed for implants, where CNTs can support osseointegration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to this, they are increasingly applied in medicine and diagnostics, including tissue engineering [1,2]. These two-dimensional carbon structures are used, among others, to functionalize materials designed for implants, where CNTs can support osseointegration [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…MWCNTs can precipitate HA crystals [73], and this property is believed to enhance bone affinity by efficiently depositing HA that serves as a bone matrix at the site of bone regeneration. In addition, we have previously reported that MWCNT blocks showed excellent protein adsorption [51,74] (Figure 2). In addition, many studies have reported that MWCNTs showed good adsorption of proteins such as BSA (bovine serum albumin) and immunoglobulin G (IgG) [75], suggesting that it is an excellent scaffold for regenerative medicine in terms of its ability to maintain and provide a sustained release of growth factors.…”
Section: Chemical Properties Of Cntsmentioning
confidence: 78%
“…Scaffolds require the in vivo ability to adsorb and retain growth factors that are secreted by their own cells [51] and to facilitate the sustained release of artificial growth factors [52]. Promising materials for bone regenerative medicine include scaffolds made of biodegradable materials such as PLGA [53] and hydrogel [54], in addition to porous hydroxyapatite scaffolds with coated surface modifications [55], all of which have been reported to provide a good sustained release of growth factors such as BMP-2.…”
Section: Chemical Properties Of Scaffoldsmentioning
confidence: 99%
“…The designed porous CNTs demonstrated good osteoconductive ability, cell attachment and proliferation capacity, and growth factor retaining ability. A triblock of maximized mechanical strength MWCNTs containing BMP‐2 protein has also shown the formation of ectopic bone when implanted in mice that could serve as filler for bone defects . Scaffolds containing graphene oxide and hydroxyapatite NPs have been prepared using self‐assembly and showed an increase in proliferation and activity of alkaline phosphatases in rat bone MSCs to stimulate mineralization and bone healing .…”
Section: Bone Tementioning
confidence: 99%
“…A triblock of maximized mechanical strength MWCNTs containing BMP-2 protein has also shown the formation of ectopic bone when implanted in mice that could serve as filler for bone defects. 77 Scaffolds containing graphene oxide and hydroxyapatite NPs have been prepared using self-assembly and showed an increase in proliferation and activity of alkaline phosphatases in rat bone MSCs to stimulate mineralization and bone healing. 78 Osteoblast adhesion and proliferation has also been enhanced by scaffolds containing bacterial cellulose isolated from Gluconacetobacter xylinus and MWCNTs suggesting their role in bone regeneration.…”
Section: Bone Tementioning
confidence: 99%